2015
DOI: 10.1002/ece3.1468
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of oomycete pathogens from Phragmites australis‐invaded and noninvaded soils to seedlings of wetland plant species

Abstract: Soil pathogens affect plant community structure and function through negative plant–soil feedbacks that may contribute to the invasiveness of non-native plant species. Our understanding of these pathogen-induced soil feedbacks has relied largely on observations of the collective impact of the soil biota on plant populations, with few observations of accompanying changes in populations of specific soil pathogens and their impacts on invasive and noninvasive species. As a result, the roles of specific soil patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 92 publications
3
27
0
Order By: Relevance
“…Importantly, richness reveals very little about pathogen load or pressure and it is still possible that the two lineages are experiencing different levels of pathogen pressure given differences in pathogen virulence on each plant lineage or surrounding plants (Crocker et al. , Allen et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, richness reveals very little about pathogen load or pressure and it is still possible that the two lineages are experiencing different levels of pathogen pressure given differences in pathogen virulence on each plant lineage or surrounding plants (Crocker et al. , Allen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…We know that some oomycetes have lineage‐specific virulence in Phragmites (Crocker et al. ), and that the roles of many endophytic fungi and bacteria are plant and genotype specific (Schulz and Boyle , Hardoim et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies with P. australis have described distinct oomycete, archaea, and bacteria communities from rhizosphere soil of native and European P. australis lineages in North America (Nelson and Karp , Crocker et al. , Yarwood et al. , Bowen et al.…”
Section: Methodsmentioning
confidence: 99%
“…(, ), which demonstrated that various Pythium oomycetes differed in their virulence to seedlings of several wetland plant species based on the P. australis lineage they were isolated from (Crocker et al. ), whereas the impact of bulk soil did not differ between lineages (Crocker et al. ).…”
Section: Methodsmentioning
confidence: 99%